La Araucanía profunda: El problema de la identidad y de la representación de rotos y fronterizos. De la Guerra de Ocupación a la Postguerra (1862 a la década de 1910) (Revista de História Regional, 2021)
Abstract: In a dialogue between the past and the present, we analyze the period comprised between the war of Occupation of Araucanía and the post-war period (from 1862 to the 1910s). We see this period as a key moment in the implementation of the project of state modernization and construction of alterity among the subjects and actors involved: The State, the colonists, the Mapuche, and the Chilean-mestizo. This article seeks to explain why the Chilean-mestizos (rotos and former frontiersmen) have been poorly represented in the identity of the Araucanía and in the conflicts or issues that characterize this region, despite their numerical significance and their decisive participation in the modernization process. From historiography and philosophy, the categories of transit and identity breakdown are proposed and analyzed to explain this phenomenon, which is also considered an attempt to immerse ourselves in what is identified in these lines as the Araucanía Profunda: the individuals scarcely represented. Key words: Araucanía Profunda, rotos, frontiersmen, transit, identity breakdown.